Development of the elderly health monitoring system through families and community health workers during the COVID-19 pandemic - Putri T Rosha; Annisa Ryan Susilaningrum; Anisah Ramadhani; Anggi Lukman Wicaksana; Firdaus Hafidz (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2022)
Elderly people have a high risk of severe and fatal COVID-19 condition. Controlling the risk factors among the elderly is important, but health service provision during outbreaks is challenging. The elderly need increased attention to be monitored for their health status routinely. The elderly must also adjust daily activities according to the COVID-19 protocols. This program aimed to provide a practical example of a feasible system to empower community health workers and families for monitoring health among the elderly. This study used quantitative and qualitative data to identify the problems and needs of elderly health monitoring in Caturtunggal, Sleman, Indonesia. Descriptive quantitative methods used secondary data from the Sleman Health and Demographic Surveillance System and elderly health checklists to identify the issues of non-communicable diseases (NCDs) before and during COVID-19. The community health workers were interviewed to explore the needs and feasibility of programs among the elderly. As much as 16% of Caturtunggal population is elderly. One-third are 60-65 years old (33.30%) and retired (30.60%). The most common NCDs were hypertension (25.60%), diabetes mellitus (13.30%), stroke and coronary heart disease (4.40% for each). Almost all elderly (88.89%) have health insurance. Health counselling, online consultation, and monitoring were agreed on after discussion with the community health workers. Serial consultations (COVID-19 protocol for elderly, regular self-monitoring, the national health insurance mobile application, and health services during the pandemic situation) were conducted through WhatsApp groups. Free counseling was provided throughout the program for the elderly care during the outbreak. The monitoring was achieved through the WhatsApp groups by delivering instructional photos or videos of physical activity, blood pressure measurements, dietary record and stress management. The elderly and families felt more confident to check their health status and reported the results. In conclusion, development of health monitoring system was conducted through health checklists. Family and community cadres were also involved to make the program more feasible and sustainable.